MATERNAL PROTEIN MALNUTRITION DURING LACTATION PREDISPOSES TO A METABOLIC SYNDROME PHENOTYPE IN MALE WISTAR RATS - Willian do Nascimento de Souza Rodrigues; Maria Natalia Chimirri Peres; Scarlett Rodrigues Raposo; Maryana Debossan Fernandes; Marcos Vinícius Martins; Leticia Ferreira Barbosa; Filipe Lima dos Santos; Lucas Paulo Jacinto Saavedra; Veridiana Mota Moreira; Paulo Cezar de Freitas Mathias (Arquivos do Mudi, 2023)
Maternal nutritional insults during lactation can modulate the offspring phenotype associatedwith the risk of non-communicable diseases at different stages of ontogenetic development.The aim of this research was to analyze biometric and biochemical parameters of male Wistarrats, born to dams fed a low-protein diet in the first two-thirds of lactation. Therefore, themothers received ad libitum a normal (NP, 23%) or low-protein (LP, 4%) diet, originatingtwo experimental groups that were evaluated at 14 days old (NP-14 and LP-14). The resultsshowed that the LP-14 offspring male rats had lower body weight (p<0.0001), reduced liver(p<0.0001) and higher brown fat deposits (p<0.0001), compared to the equivalent control.They also exhibited hyperglycemia (p<0.05), hypercholesterolemia (p<0.0001), and increasedserum β-hydroxybutyrate (p<0.0001), contrasting with reduced triglycerides (p<0.05) levels.We conclude that maternal exposure to a low-protein diet during lactation was able toprogram 14-day-old male neonates to develop a metabolic syndrome phenotype, probably dueto restriction of body and visceral growth in these animals.